NURSE'S KNOWLEDGE LEVEL OF HANDLING EMERGENCY PATIENTS DUE TO TRAFFIC ACCIDENTS AT RSUD PARAPAT SIMALUNGUN REGENCY - Sondang Sidabutar; Christian Rayando Butar Butar; Diana Lorenta Barimbingan (RADJA PUBLIKA, 2022)
Traffic accidents can cause loss of a person or disability as well as injuries that require immediate help, such as hard object trauma to the head which can cause nerve disorders, failure in an organ such as respiratory failure and kidney failure, loss of fluids and electrolytes in large quantities, bleeding, and trauma or injury to the musculoskeletal system. Hospitals as health care facilities that have health workers must be able to provide optimal health services, especially for patients who are in an emergency condition. Efforts to provide health services to emergency patients are basically able to prevent death or disability that may occur. A study was carried out on 32 respondents (nurses) which aimed to determine the level of knowledge of nurses about handling emergency patients due to traffic accidents at the Emergency Unit of Parapat General Hospital, where this research is descriptive in nature, and uses totally sampling (the whole population), namely totaling 32 people, and carried out using primary data obtained from distributing questionnaires. After data processing was carried out, it was found that the majority of respondents had sufficient knowledge, namely around 20 people (62,500%) and had good knowledge, around 6 people (18,750%), less knowledgeable, around 6 people (18,750%) based on the level of education, the majority of respondents had sufficient knowledge, namely around 20 people (62.500%) and good knowledge about 6 people (18.750%).